Leniency and Severity in China’s Death Penalty Debate - Lewis, Margaret K. (Columbia Journal of Asian Law, 2011)
China has implemented an initial wave of death penalty reforms that returned final review power of all capital cases to the Supreme People’s Court and reportedly significantly curbed executions. After reviewing recent legal developments concerning capital cases, this Article explores how the initial push to reduce use of the death penalty has given way to a more complex and nuanced debate over what factors should determine when the death penalty is appropriate. At this juncture in the reform trajectory, the dilemma of when to be lenient and when to be severe is particularly acute as public opinion chafes against a rapid decline in executions, especially when those treated leniently are affluent and/or politically well-connected.